2020
DOI: 10.1109/access.2020.3014441
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Knowledge Transfer for Object Detection in Marine Environmental Monitoring and Exploration

Abstract: The volume of digital image data collected in the field of marine environmental monitoring and exploration has been growing in rapidly increasing rates in recent years. Computational support is essential for the timely evaluation of the high volume of marine imaging data, but often modern techniques such as deep learning cannot be applied due to the lack of training data. In this paper, we present Unsupervised Knowledge Transfer (UnKnoT), a new method to use the limited amount of training data more efficiently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Furthermore, for sub-sea imaging, most groups gather images using custom built imaging hardware, where in [28] the authors reported that even small differences in sub-sea imaging hardware limits learning transferability and distorts deep learning classifier outputs. In [29] a pipeline to make training datasets transferable for inference on images from other datasets is proposed for segmentation of marine organism. The work proposes how to reduce scale variance across multiple datasets, which is highlighted as an important consideration for seafloor imagery.…”
Section: Supervised Learningmentioning
confidence: 99%
“…Furthermore, for sub-sea imaging, most groups gather images using custom built imaging hardware, where in [28] the authors reported that even small differences in sub-sea imaging hardware limits learning transferability and distorts deep learning classifier outputs. In [29] a pipeline to make training datasets transferable for inference on images from other datasets is proposed for segmentation of marine organism. The work proposes how to reduce scale variance across multiple datasets, which is highlighted as an important consideration for seafloor imagery.…”
Section: Supervised Learningmentioning
confidence: 99%
“…A well-known and effective method for improving the generalizability of a DL model is to use regularization (Kukacˇka et al, 2017). Some of the regularization methods applied to fish and marine habitat monitoring domains include transfer learning (Zurowietz & Nattkemper, 2020), batch normalization (Islam et al, 2020), dropout (Iqbal et al, 2021) and using a regularization term (Tarling et al, 2021).…”
Section: Model Generalizationmentioning
confidence: 99%
“…A well-known and effective method for improving the generalisability of a DL model is to use regularisation [87]. Some of the regularisation methods applied to fish and marine habitat monitoring domains include transfer learning [88], batch normalisation [57], dropout [81], and using a regularisation term [62]. Since it is difficult to obtain a large labelled dataset, various techniques have been proposed to address this challenge.…”
Section: Challenges and Ap-proaches To Address Themmentioning
confidence: 99%